Musculoskeletal loads in ergometer rowing - Hase, K.; Kaya, M.; Zavatsky, A. B.; Halliday, S. E. (Journal of Applied Biomechanics, 2004)
Rowing ergometers can be found in most gyms and fitness centers, but many people who use them regularly have little or no instruction in rowing technique. It is not known whether nonrowers who regularly practice ergometer rowing are at risk of musculoskeletal problems. This study was done to quantify the differences in kinematics, kinetics, and musculoskeletal loading of competitive rowers and nonrowers during ergometer rowing. An experiment was performed to collect kinematic, external force, and EMG data during ergometer rowing by 5 university-level competitive rowers and 5 nonrowers. Kinematic and external force data were input to a 3-D whole-body musculo-skeletal model which was used to calculate net joint forces and moments, muscle forces, and joint contact forces. The results showed that competitive rowers and nonrowers are capable of rowing an ergometer with generally similar patterns of kinematics and kinetics; however, there are some potentially important differences in how they use their legs and trunk. The competitive rowers generated higher model quadriceps (vastus) muscle forces and pushed harder against the foot cradle, extending their knees more and their trunks less than the nonrowers during the drive phase. They also had higher contact forces at the knee and higher peak lumbar and knee flexion moments. The ratio of average peak vastus force to average peak erector spinae force in the experienced rowers was 1.52, whereas it was only 1.18 in the nonexperienced rowers.